TINJAUAN ATAS IMPLEMENTASI PERPANJANGAN MASA ANGSURAN UNTUK PEMBIAYAAN DI BANK SYARIAH PADA SITUASI PANDEMI COVID-19 - Muhammad Ubaidillah; Rizqon Halal Syah Aji (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2020)
Covid-19 pandemic has occurred in almost all countries in the world. The pandemic has caused millions of people to find it difficult to pay off credit or financing installments due to declining daily income. If these conditions are not properly addressed, it will cause a country's economic growth to decline. This article aims to examine the application of the Surah Al Baqarah verse 280 to the granting of credit or financing restructuring to debtors affected by the Covid-19 pandemic. The literature review method is used in this article. In addition, this article also uses descriptive analysis methods to describe the phenomena that occur in the field. The study conducted in this article shows that the application of Surah Al Baqarah verse 280 at the time of the Covid-19 pandemic can be a solution to maintain Indonesia's economic growth rate.